Determinants of Stunting Children (0-59 Months) in Some Countries in Southeast Asia - Eka Rosiyati; Erlina A.D. Pratiwi; Ina Poristinawati; Erna Rahmawati; Resita Nurbayani; Sri Lestari; Putri Sari Wardani; Muhammad Ridho Nugroho (STIKes Hang Tuah Pekanbaru, 2019)
Background: Stunting is one of the main nutritional problems caused by malnutrition in children under 5 years old. Risk factors of stunting influenced by socio-economic, Infant and Young Child Feeding (IYCF), child ilnesses, Water Sanitation and Hygiene (WASH). These factors vary considerably accros the nation in southeast asia. Defines determinant is needed to identified the right intervention. Methodology: This systematic review was conducted using the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidenlines. Articles were searched by using pubMed database. The literature search outline in the methods indentified 14.790 articles discuss stunting. We identified 60 articles potentially met all criteria using PubMed advanced search strategy. A total of 60 articles were retrieved from one database (PubMed), 11 articles met the inclusion criteria for stunting in Southeast Asia countries. Result: In our review socio-economic status was reported as one of consistent factors associated with stunting in Cambodia, Myanmar, Indonesia, Laos, Thailand and Malaysia. Low household income and lack education of mother influenced unappropriated IYCF practice, poor hygiene and sanitation and care of child illnesses. Conclusions: Improving socio-economic like income and maternal exposure to nutrition and health information especially for the topics of growth and development, appropriated IYCF, hygiene, sanitation, and child illnesses are requires continuous improvement in a specific strategy that involves many factors.